2021
DOI: 10.3390/fishes6040071
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability of Parasite Communities: Implications for Fish Stock Identification

Abstract: The spatial and temporal variability of parasite communities have received little attention when used as biological tags for identifying fish stocks. This study evaluated the potential spatial and temporal variability of the parasite communities affecting three marine fish species collected between 1993 and 2017. To avoid the potential effect of host age in parasite communities, individuals of similar ages were selected: 1123 Engraulis ringens (12–24 months old), 1904 Trachurus murphyi (24–36 months old), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Thus, in general, these component communities were characterized by a rather low diversity, but were well-ordered communities with a nested structure, as assessed by the NODF index ( Table 5 ). Stable parasite community structures, despite relatively low infection indices in fish hosts, have been also reported for other aquatic systems [ 35 , 111 , 112 , 113 ]. Moreover, similar results have recently been reported for two members of the family Sparidae ( Pagrus pagrus and Pagellus bogaraveo ) from the western Mediterranean Sea by Lablack et al [ 36 ], who found a homogeneous taxonomic composition of parasite communities for common taxa but not homogeneous for rare taxa (i.e., about the same as took place for Spicara smaris in the Crimean waters ( Figure 5 j)), suggesting a similar use of a common local pool of helminths.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Thus, in general, these component communities were characterized by a rather low diversity, but were well-ordered communities with a nested structure, as assessed by the NODF index ( Table 5 ). Stable parasite community structures, despite relatively low infection indices in fish hosts, have been also reported for other aquatic systems [ 35 , 111 , 112 , 113 ]. Moreover, similar results have recently been reported for two members of the family Sparidae ( Pagrus pagrus and Pagellus bogaraveo ) from the western Mediterranean Sea by Lablack et al [ 36 ], who found a homogeneous taxonomic composition of parasite communities for common taxa but not homogeneous for rare taxa (i.e., about the same as took place for Spicara smaris in the Crimean waters ( Figure 5 j)), suggesting a similar use of a common local pool of helminths.…”
Section: Discussionmentioning
confidence: 67%
“…As a result, classical diversity indices (Shannon, Pelou’s evenness, Berger–Parker, and others) have been involved in parasitological studies [ 30 , 31 , 32 , 33 , 34 ]. Helminth communities have been shown to vary spatially and temporally [ 35 , 36 ] depending on historical, biogeographical, and ecological factors [ 37 , 38 ], among which the total abundance and, therefore, the availability of potential hosts, has been recognized as being the most important [ 39 , 40 ]. Other significant factors driving fish parasite faunas are characteristics of the locality, predator–prey relationships, relationships between different phylogenetic groups of parasites, and stochastic processes across multiple scales and intensities [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…United States and Canadian mariculture industries similarly urged fish parasitologists to target L. salmonis in their research (Burka et al , 2012). The North American catfish farming industry (Engle et al , 2022) was also a cradle for aquaculture parasitology. Russian aquaculture dates back several centuries.…”
Section: Parasites In Aquaculturementioning
confidence: 99%
“…(2022) observed similar results on parasites of clupeiform fish in South Atlantic, indicating that fish species is a strong determinant for parasite diversity, especially their diet composition and infection by endoparasites as nematodes, which are mostly transmitted by food chain links in marine environments (Lafferty, 2013). It should be highlighted that several approaches including parasite diversity estimations use parasites as biological tags for discriminating host populations from the South Atlantic and Pacific Oceans, where nematodes always show representative richness in the parasite communities (Timi, 2003; Timi et al ., 2005, 2010; Braicovich and Timi, 2010; Canel et al ., 2019; Espínola-Novelo and Oliva, 2021).…”
Section: Patterns Of Nematode Diversity Associated With Host Taxamentioning
confidence: 99%